Fog Computing and its Security Issues - Keerthi, TR; Agarwal, Mohit (International Journal of Computer Sciences and Engineering, 2025)
Fog Computing is another worldview that increases the Cloud storage through figuring assets on the edges of a system. It is clearly well described as a cloud-like stage containing comparative information, computation and application administrations, yet is on a very basic level diverse in that it is decentralized. Furthermore, Fog computing are equipped for preparing a lot of information locally, work on-premise and are completely convenient. It can be on mixed equipment’s. These highlights make the Fog stage extremely reasonable for time and area for touchy applications. For instance, Internet of Things (IoT) Devices having lot of information and its required rapidly process for working. This large area of usefulness driven applications increases numerous confidentiality issues with respect to information, virtualization, isolation, organize, malware and observing. This paper reviews existing papers on Fog figuring applications to resolve regular security holes. Comparable advancements like Edge figuring, Cloudlets and Micro-server farms having same incorporated to give a comprehensive audit process. Most of Fog applications are roused by the longing for usefulness and end-user prerequisites, while the confidentiality aspects are frequently disregarded or measured as a bit of hindsight. This paper also determines the effect of those security issues and conceivable solution, giving prospect security-pertinent headings to those responsible for designing, emerging, and preserving Fog systems